Telemedicine platform for outpatient and emergency care during the COVID-19 pandemic (Research, Society and Development, 2022)
Telemedicine is defined as the provision of health services virtually, to diagnose treatments, make appointments and prior consultations, and also in preventing diseases. The coronavirus disease (COVID-19), the agent responsible for the current pandemic, was able to cause the widespread transmission to individuals of all ages. In such a way, the need for investments in an adequate structure, with the availability of equipment and the provision of connection of an intuitive and secure telemedicine platform, which offers end-to-end encryption. The objective of this work was to implement a telemedicine platform in a local Hospital, which intends to guarantee humanitarian and efficient care free of charge, in various areas of the health system applied at the Regional University Hospital of Maringá. Several studies demonstrate the need for adaptations, where facilities work together promoting virtual service through Telemedicine platforms, guaranteeing great potential in reducing viral transmission during the pandemic, since, through the reduction of the transit of infected or suspects, it is believed that, due to the proposed objective, there is a reduction in the risks of contamination caused by individual contact, and transmission mainly of COVID-19.